THE ESSENCE OF MODELING AND SEGMENTATION OF THE KARAKALPAK AND UZBEK LANGUAGES - Munisa Xudoyberganova (Sciental Journals Publishing, 2025)
This article explores the modeling and segmentation of the Karakalpak and Uzbek languages within the framework of computational linguistics and Natural Language Processing (NLP). Given their shared agglutinative morphological structure, both languages require detailed morphological, syntactic, and semantic analysis for effective computational processing. The study emphasizes the importance of accurate segmentation—at sentence, word, and morpheme levels—as a foundational step for various NLP applications, including machine translation and morphological parsing. It also addresses the underrepresentation of Karakalpak in digital linguistic resources, advocating for the creation of structured parallel corpora.